Persistent Herpes Virus Infections and Their Role in the Incidence in Frequently and Chronically Ill Children - Ye.I. Yulish; S.Ya. Yaroshenko (Zaslavsky O.Yu., 2013)
We analyzed data on the role of herpes virus persistent infections in recurrent course of respiratory diseases in frequently and chronically ill children. The approaches to the etiopathogenic therapy and rehabilitation with the use of flavonoids were considered.